THE ESSENCE AND COMPONENTS OF THREATS TO THE ECONOMIC SECURITY OF HIGHER EDUCATION INSTITUTIONS - Victoria M. Varenyk; Iryna M. Miro; Zoia S. Pestovska (Academy Review)
A higher education institution is both a social institution and a commercial enterprise in the educational services market. Ensuring the economic security of private higher education institutions involves identifying risks and threats to this security (especially as they cannot rely on state support), which justifies the purpose and objectives of the paper. To ensure economic security, it is necessary to develop a certain concept, management mechanism, model, or set of measures. However, it is essential first to identify, measure, and assess the relevant risks, dangers, and threats. Threats to the economic security of a private higher education institution are considered in the context of its components, with a view to identifying them and assessing their potential, based on the list of tasks outlined for higher education institutions in Article 25 of the Law of Ukraine ‘On Higher Education.’ It is proven that risk is the probability of the negative impact of certain events, threat is a set of specific factors that can negatively affect activities, and danger is a specific, identified condition which, if ignored, can lead to significant losses. Therefore, the category of threat was chosen as a set of certain factors that can have a negative impact; factors that are more remote than danger, making them more suitable for identification and forecasting. The list of threats has been expanded according to the following criteria: - by the nature of implementation: overt - obsolescence of equipment, programs, technologies; covert - hacker attacks; - by the mechanism of influence: indirect - lack of motivation among teachers for research, advanced training, or the introduction of innovative teaching methods; direct - an overly large administrative apparatus, irrational management structure and division of responsibilities, or insufficient control; - by the place of origin: internal threats, as threats can also originate within the institution - insufficient qualifications of top management, reluctance of teachers to develop, sabotage of new technologies, corruption or bribery, unethical behavior. The authors identifie threats to each component of the economic security of a private higher education institution and presents possible responses to these threats. Assessing the level of economic security of a higher education institution using statistical methods is challenging, so it is proposed that future assessments focus on the damage caused to the institution’s interests and the effectiveness of preventative measures, based on the indicator method. It is concluded that a security category can exist only in the presence of threats. Thus, the existing classifications of threats to the economic security of a private higher education institution are clarified and supplemented. The components of economic security are compared with the legally established tasks, principles, rights, and obligations of a higher education institution, a list of threats to the economic security of a private higher education institution by its components is developed, and possible responses to these threats are recommended.